2013
DOI: 10.1186/1756-3305-6-102
|View full text |Cite
|
Sign up to set email alerts
|

Redescription of Hepatozoon felis (Apicomplexa: Hepatozoidae) based on phylogenetic analysis, tissue and blood form morphology, and possible transplacental transmission

Abstract: BackgroundA Hepatozoon parasite was initially reported from a cat in India in 1908 and named Leucocytozoon felis domestici. Although domestic feline hepatozoonosis has since been recorded from Europe, Africa, Asia and America, its description, classification and pathogenesis have remained vague and the distinction between different species of Hepatozoon infecting domestic and wild carnivores has been unclear. The aim of this study was to carry out a survey on domestic feline hepatozoonosis and characterize it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
142
2
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(161 citation statements)
references
References 38 publications
14
142
2
3
Order By: Relevance
“…The sequencing of the PCR products amplified from the cat samples in this study showed that both H. felis and H. canis can infect cats in Spain, although H. felis is by far more common, with only one cat infected with H. canis . A similar higher ratio of H. felis versus H. canis infection in domestic cats was also found in a study from Israel where only two cats out of 55 Hepatozoon -spp.-positive cats were detected with H. canis infection and 53 cats out of a total of 153 tested were positive for H. felis [13]. The Hepatozoon infection prevalences described in previous Spanish studies varied from 0.6% in one study [17], 4% in cats from the Barcelona area [19] and 16% in a cat colony from Barcelona [18], compared to the prevalence in our study of 1.6%.…”
Section: Discussionsupporting
confidence: 77%
“…The sequencing of the PCR products amplified from the cat samples in this study showed that both H. felis and H. canis can infect cats in Spain, although H. felis is by far more common, with only one cat infected with H. canis . A similar higher ratio of H. felis versus H. canis infection in domestic cats was also found in a study from Israel where only two cats out of 55 Hepatozoon -spp.-positive cats were detected with H. canis infection and 53 cats out of a total of 153 tested were positive for H. felis [13]. The Hepatozoon infection prevalences described in previous Spanish studies varied from 0.6% in one study [17], 4% in cats from the Barcelona area [19] and 16% in a cat colony from Barcelona [18], compared to the prevalence in our study of 1.6%.…”
Section: Discussionsupporting
confidence: 77%
“…The exact vectors and routes of transmission of feline hepatozoonoses are not known [27], but vectorial transmission likely plays a key role as for other species of Hepatozoon in different vertebrate species such as dogs [31]. The results of the present study demonstrate the utility of the novel Hepatozoon spp.…”
Section: Discussionmentioning
confidence: 65%
“…Based on the gene target used in the current study, several Hepatozoon sequences were detected, but some samples were very similar to H. canis and H. felis. A recent PCR study on wild felids and canids in India detected H. felis only in felids (lions, tigers, and leopards) and H. canis only in canids (domestic dogs and Indian wild dogs) (Pawar et al 2012); however, these parasites are not considered to be specific to the suborders of the Carnivora and H. canis and H. felis have been reported in both canids and felids (Rubini et al 2006;Jittapalapong et al 2006;Baneth et al 2013). Similarly, in the current study, H. canis-like sequences were detected in felids (lions) and hyena and H. felis-like sequences were detected in hyenas.…”
Section: Discussionmentioning
confidence: 99%